Mapping boundaries: Microprosodic and dialectal variability in the perception of Estonian long and overlong quantity - Pärtel Lippus; Liis Kask; Sofia Lutter; Nele Põldver; Kairi Kreegipuu (Eesti Rakenduslingvistika Ühingu Aastaraamat)
This paper presents the results of a web-based perception experiment that tested the distinction of long (Q2) and overlong (Q3) quantity degrees in Estonian. Firstly, we observe an effect of segmental quality on the perception of quantity. Most of the quantity experiments have used one or two minimal triplets, typically with open back vowels, not considering variation due to intrinsic properties. The stimuli were created from words with 8 different segmental combinations. The second aim of this study is to map the dialectal variability in Estonian quantity perception. There has been some evidence that listeners from East and South dialect areas are less sensitive to pitch cue than those from North and West. The current study was carried out with 290 participants of different regional backgrounds. The results showed that different segmental quality sets have slightly different Q2–Q3 category boundaries. Also, the precision of quantity identification was considerably lower in the case of a nonsense word set. Unexpectedly, we were not able to find a clear dialectal background effect.